FREE-RADICAL OXIDATION ACTIVITY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION WITHOUT Q WAVE TREATED WITH EPROSARTAN OR ENALAPRIL ADDITIONALLY TO THE BASIC THERAPY - O. G. Zaylobidinov; Yu. N. Ziyaev; N. K. Kamilova; A. S. Khalilov; B. F. Mukhamedova (Рациональная фармакотерапия в кардиологии)
Aim. To compare effects of eprosartan and enalapril on free-radical oxidation in patients with acute myocardial infarction (AMI) without Q wave.Material and methods. 50 patients (aged 52,8±3,3 y.o.) with AMI without Q were involved into the study. Patients were randomized on 2 groups. The first group consisted of 24 patients (51,1±2,4 y.o.) which received basic therapy and enalapril (10 mg daily). The second group consisted of 26 patients (53,1±3,0 y.o.) which received basic therapy and eprosartan (600 mg daily). Basic therapy included anticoagulants, antiplatelets, beta-blockers, nitrates and statins. Intensity of free-radical oxidation was evaluated by change of serum malonic dialdehyde (MDD) concentration. Functional activity of serum enzymes of antioxidatic system (AOS) was evaluated by rate of reaction of superoxide dismutase (SOD) and catalase (CT).Results. The intensity of free-radical oxidation increased in patients with AMI without Q: high level of MDD and peroxinitrite (ONOO-). Besides activity of AOS enzymes (SOD and CT) decreased. Eprosartan reduced intensity of peroxide oxidation more prominently in comparison with enalapril. Both drugs preserved low activity of SOD and CT.Conclusion. Eprosartan was significantly more effective than enalapril in reduction of serum free-radical oxidation in patients with AMI without Q wave during 10 days after hospital admission.